2021
DOI: 10.1186/s40729-021-00353-8
|View full text |Cite
|
Sign up to set email alerts
|

Implant-prosthetic rehabilitation of patients with severe horizontal bone deficit on mini-implants with two-piece design—retrospective analysis after a mean follow-up of 5 years

Abstract: Background As a consequence of tooth loss due to trauma or extraction, a reduced alveolar crest volume limits the deployment of standard implants in certain patient cases. For this reason, minimal-invasive treatment with mini-dental implants (MDI) might be an option to allow implant treatment even in cases with severe horizontal bone loss without augmentation measures. The aim of this retrospective cohort study was to investigate clinical and radiological implant, as well as patient-related par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…[20][21][22] Previous publications have shown that primary stability has a pivotal role in success of "IL protocol"; diminished initial stability being a key factor in early implant failure. In contrast, another publication revealed a high final success rate of implants loaded immediately subjected to low insertion torques i-e < 25 N-cm [23][24][25][26][27][28][29][30] Hence, ideal value of insertion torque dictating successful osseointegration still needs to be set by conducting further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Previous publications have shown that primary stability has a pivotal role in success of "IL protocol"; diminished initial stability being a key factor in early implant failure. In contrast, another publication revealed a high final success rate of implants loaded immediately subjected to low insertion torques i-e < 25 N-cm [23][24][25][26][27][28][29][30] Hence, ideal value of insertion torque dictating successful osseointegration still needs to be set by conducting further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This means that bone resorption after tooth loss is often greater in width than in height [10]. To insert standard diameter implants (SDIs), however, a minimum bone width of 6 mm is required [11,12]. Bone augmentation can be performed to improve insufficient available bone; however, the procedure is cost-and time-intensive and can lead to complications such as infection, wound dehiscence, damage to surrounding tissue, or gingival recession [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Increased prosthetic flexibility may also be possible under certain clinical situations [ 12 ]. Furthermore, studies have reported the successful use of 2.7–3.25 mm NDIs and mini-diameter implants as a minimally invasive alternative for patients with insufficient bone ridge thickness in the posterior mandible and a reduced alveolar crest volume [ 14 , 15 ]. Another meta-analysis study described high patient satisfaction for mini-diameter implants as compared to SDIs when used for implant-supported overdentures [ 16 ].…”
Section: Introductionmentioning
confidence: 99%